2015
DOI: 10.1159/000368483
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistant Hypertension - No SIMPLE Way Out

Abstract: Hypertension poses growing challenge for health policy-makers and doctors worldwide. Recently published results of Symplicity-III trial (HTN-3), the first blinded, randomized, multicenter study on the efficacy of renal denervation for the treatment of resistant hypertension did not show a significant reduction of BP in patients with resistant hypertension 6 months after renal-artery denervation, as compared with controls. In this paper we review clinical and experimental studies on renal denervation. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…SYMPLICITY I, II and III renal denervation trials were aimed at patients with treatment resistant hypertension defined as an ABP over 140/90 mmHg despite treatment with at least 3 antihypertensive drugs, including a diuretic [33][34][35]. Although these studies did not show any advantage of renal denervation over pharmacotherapy, they did prove patient safety for the procedure [33][34][35]. SPYRAL HTN-OFF, which followed, showed that renal denervation might offer a viable antihypertensive management for patients who are not using ABP lowering medication [36].…”
Section: Renal Denervation Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…SYMPLICITY I, II and III renal denervation trials were aimed at patients with treatment resistant hypertension defined as an ABP over 140/90 mmHg despite treatment with at least 3 antihypertensive drugs, including a diuretic [33][34][35]. Although these studies did not show any advantage of renal denervation over pharmacotherapy, they did prove patient safety for the procedure [33][34][35]. SPYRAL HTN-OFF, which followed, showed that renal denervation might offer a viable antihypertensive management for patients who are not using ABP lowering medication [36].…”
Section: Renal Denervation Clinical Trialsmentioning
confidence: 99%
“…SPYRAL HTN-OFF, which followed, showed that renal denervation might offer a viable antihypertensive management for patients who are not using ABP lowering medication [36]. The effectiveness of renal denervation is mechanistically tied to sympathetic nervous system inhibition [33]. Considering that non-selective beta-blockers are utilized to lower IOP, it could be hypothesized that renal denervation could simultaneously decrease ABP and IOP [37], thus offering a viable alternative to pharmacotherapy in patients with both glaucoma Janusz Skrzypecki et al, Blood pressure and glaucoma and hypertension.…”
Section: Renal Denervation Clinical Trialsmentioning
confidence: 99%